2019
DOI: 10.1016/j.probengmech.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning solution approach for high-dimensional random differential equations

Abstract: Developing efficient numerical algorithms for the solution of high dimensional random Partial Differential Equations (PDEs) has been a challenging task due to the well-known curse of dimensionality. We present a new solution framework for these problems based on a deep learning approach. Specifically, the random PDE is approximated by a feed-forward fully-connected deep residual network, with either strong or weak enforcement of initial and boundary constraints. The framework is mesh-free, and can handle irreg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…Another appealing approach that exploits the variational form of PDEs is considered in [9,10,11]. In [9], a committer function is parameterized by a neural network whose weights are obtained by optimizing the variational formulation of the corresponding PDE.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Another appealing approach that exploits the variational form of PDEs is considered in [9,10,11]. In [9], a committer function is parameterized by a neural network whose weights are obtained by optimizing the variational formulation of the corresponding PDE.…”
Section: Related Workmentioning
confidence: 99%
“…In [9], a committer function is parameterized by a neural network whose weights are obtained by optimizing the variational formulation of the corresponding PDE. In [10], deep learning technique is employed to solve low-dimensional random PDEs based on both strong form and variational form. More recently, an adaptive collocation strategy is presented for a method in [27].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Largaris et al [14] and more recently Berg and Nyström [16] showed fully connected networks can be used to learn PDE solutions on even complex domains. Recently, several investigators have examined the use of variational formulations of the governing equations as loss functions to solve various PDEs [3,17,18,19] which has been proven to be effective. Sirignano et al [20] show that the use of a fully connected network can be used for efficiently solving PDEs of high dimensionality where traditional discretization techniques become unfeasible.…”
Section: Introductionmentioning
confidence: 99%